Patients with geriatric syndromes and anti-amyloid therapies: lack of consideration? An exploratory analysis of the literature - Sadlon, Angélique; Ott, Martin; Kressig, Reto W. (Frontiers in Aging Neuroscience, 2023)
Introduction: patients who should benefit from anti-amyloid therapies (AAT) are found across all geriatric settings. Yet, it remains unclear how the use of AAT in patients with geriatric syndromes, such as frailty and polypharmacy, has so far been discussed in the literature.Methods: articles on aducanumab, gantenerumab, lecanemab, donanemab, crenezumab, solanezumab were retrieved in MEDLINE from inception to July 2023. For each article, identified geriatric relevant terms were assigned to five discussion contexts (eligibility of AAT study population, safety, prescription, patient clinical profile, alternative outcomes measurement). Article type and the involvement of geriatric healthcare professionals as an author were further extracted.Results: out of 538 articles, 23 (4.27%) were published in journals from the geriatric category, 44 (8.18%) included an author affiliated with a geriatric institution. One hundred and sixteen (21.56%) articles included at least one geriatric relevant term, which were mostly discussed in the context of safety and eligibility. Articles mentioning geriatric syndromes were more frequently authored by a geriatric healthcare professional (P=0.044).Discussion: the use of AAT in patients with geriatric syndromes has so far received poor attention in the literature raising concerns on their use in this patient group. The involvement of geriatric healthcare professionals in future studies may increase the relevance of AAT research in patients with geriatric syndromes.